Underdogs : the Making of the Modern Marine Corps - O'Connell, Aaron B., 1973- (Harvard University Press, 2012)
"The Marine Corps has always considered itself a breed apart. Since 1775, America's smallest armed service has been suspicious of outsiders and deeply loyal to its traditions. Marines believe in nothing more strongly than the Corps' uniqueness and superiority, and this undying faith in its own exceptionalism is what has made the Marines one of the sharpest, swiftest tools of American military power. Along with unapologetic self-promotion, a strong sense of identity has enabled the Corps to exert a powerful influence on American politics and culture. Aaron O'Connell focuses on the period from World War II to Vietnam, when the Marine Corps transformed itself from America's least respected to its most elite armed force."--Provided by publisher